Interaction Study and Reactivity of ZrIV‐Substituted Wells–Dawson Polyoxometalate towards Hydrolysis of Peptide Bonds in Surfactant Solutions. Issue 11 (2nd February 2016) - Quanten, Thomas; Shestakova, Pavletta; Van Den Bulck, Dries; Kirschhock, Christine; Parac‐Vogt, Tatjana N.
Abstract: The interaction between the 1:2 Zr IV :Wells–Dawson complex, K15 H[Zr(α2 ‐P2 W17 O61 )2 ] (1 ), and a range of surfactants was studied in detail with the aim of developing metal‐substituted POMs as potential artificial proteases for membrane proteins. The surfactants include the positively charged cetyl(trimethyl)ammonium bromide (CTAB), the negatively charged sodium dodecyl sulfate (SDS), the neutral Triton X‐100 (TX‐100), and zwitterionic 3‐[dodecyl(dimethyl)ammonio]‐1‐propanesulfonate (Zw3‐13) and 3‐[dimethyl(3‐{[(3α, 5β, 7α, 12α)‐3, 7, 12‐trihydroxy‐24‐oxocholan‐24‐yl]amino}propyl)ammonio]‐1‐propanesulfonate (CHAPS). A combination of multinuclear 1 H, 13 C, and 31 P NMR spectroscopy, 1 H diffusion‐ordered NMR spectroscopy ( 1 H DOSY), and nuclear Overhauser effect spectroscopy (NOESY) was used to examine the interaction between1 and each surfactant on the molecular level. Cationic surfactant CTAB caused precipitation of1 due to strong electrostatic interactions, while the anionic SDS and neutral TX‐100 surfactants did not exhibit any interaction at neutral pD. 1 H DOSY NMR spectroscopy indicated an interaction between1 and zwitterionic surfactants Zw3‐12 and CHAPS, which occurs via the positively charged ammonium group in the surfactant molecule. In the presence of anionic, neutral, and zwitterionic surfactants, 1 preserves its catalytic activity towards the hydrolysis of the peptide bond in the dipeptide glycyl‐l ‐histidine (GH). The fastest hydrolysis was observed at pD 7.0 and could be rationalized by taking into account pD‐dependent speciation of1 and coordination properties of GH. Abstract : K15 H[Zr(α2 ‐P2 W17 O61 )2 ] and a range of surfactants were found, by means of NOESY and 1 H and 31 P DOSY, to interact with each other in an electrostatic manner. In addition, in the presence of these surfactants K15 H[Zr(α2 ‐P2 W17 O61 )2 ] retained its catalytic nature towards the hydrolysis of the peptide bond in the dipeptide glycyl‐l ‐histidine (see figure).